An integrated approach for the characterization of wild Crocus species adopting phenotypical and phytochemical traits. (October 2022) - Siracusa, Laura; Onofri, Andrea; Galesi, Rosario; Impelluso, Carmen; Pulvirenti, Luana; Ruberto, Giuseppe; Gresta, Fabio; Spampinato, Giovanni; Cristaudo, Antonia
Abstract: Crocus is a taxonomically complex genus, characterized by high intra- and inter-specific variability. Five wild Crocus taxa - Crocus biflorus, C. longiflorus, C. neapolitanus, C. siculus and C. thomasii from three different areas of Southern Italy (Calabria, Basilicata and Sicily) have been investigated. We considered both flower morphological traits (inner and outer perigone segments, style branches and anthers) and the chemical profile of specialised metabolites (apocarotenoids: crocins; flavonoids: flavonols) in style branches, which were determined by high-performance liquid chromatography, coupled with a diode array detector and mass spectrometry (HPLC-UV-DAD-ESI-MS). Saffron ( C. sativus ) was also included as the 'control' species. The length of perigone tube, outer and inner tepals, anthers and style branches gave the highest contribution to the discrimination of different taxa. Concerning the specialised metabolite profiles, 20 flavonols and 24 crocins have been identified and quantified in the Crocus extracts and used to discriminate among samples, confirming that Crocus taxa can be considered as an important natural source of these substances. The chemical profiles of the different populations showed some distinctive qualitative and quantitative patterns that contributed to a certain degree of discrimination among species, in fact, flavonoids content range is comprised between 2.7 and 145.9 mg/g, whereas crocins range between 19.8 and 604.0 mg/g. It is thus hypothesized that the combination of morphological and phytochemical screenings may be an effective methodology to characterize wild Crocus genotypes from Southern Italy, also in comparison to C. sativus (saffron). Graphical abstract: Sixteen samples of wild Crocus belonging to five species collected in southern Italy have been studied. Morphological traits and content of carotenoids and flavonoids have been evaluated and compared. Image 1 Highlights: Morphological and phytochemical traits effectively characterized wild Crocus genotypes. Lengths of perigone tube, tepals, anthers and style branches discriminated Crocus taxa. Twenty flavonols and twenty-four crocins have been quantified in the Crocus extracts. Wild Crocus taxa may be an alternative rich source of crocins and flavonols.